SUBSTITUSI TEPUNG SINGKONG TERHADAP TEPUNG TERIGU DAN PENAMBAHAN PROTEIN DALAM PEMBUATAN MI KERING [SUBSTITUTION OF CASSAVA FLOUR TO WHEAT FLOUR AND THE ADDITION OF PROTEIN IN MAKING DRY NOODLE] - Hardoko Hardoko; Priscilla Fransisca; Titri Mastuti Siratantri (FaST : Jurnal Sains dan Teknologi, 2020)
Cassava flour is a local Indonesian food that has the potential to reduce the use of wheat flour in making noodles. However, cassava flour has sticky physical characteristics because the high amylopectin may be overcome by adding protein. The purpose of this study is to utilize cassava flour in the manufacture of dried noodles that have good physical characteristics. Another goal is to determine the level of substitution of cassava flour to wheat flour and the addition of a type of protein source and its concentration that can produce the best dry noodles. The research method used was an experimental method by making phase 1 treatments, namely protein type (control / without protein addition, ISP 5%, ISP 10%, egg 5%, egg 10%, egg 15%) in the manufacture of cassava flour substitute dry noodles, and stage 2 treatments namely the level of substitution of cassava flour (20, 30, 40%) and the best protein concentration of stage 1 plus or minus 2.5%). The results showed that the addition of eggs produced dry noodles with better physical and hedonic characteristics than control noodles or noodles with the addition of ISP. The best physical characteristics of noodles result from the addition of 15% eggs. In the Phase 2 experiment it was found that substitution of 20% cassava flour and the addition of 15% eggs produced noodles with the best physical and hedonic characteristics. The dried noodles meet SNI standards and contain 4.50% water, 1.94% ash, 13.7% protein, 2.46% fat, 168.66% water absorption, cooking loss 6.63%, springiness 0, 98 mm, adhesiveness 24.07 gs, and overall hedonic value of 5.25 ± 1.02 (hedonic scale 1-7).Cassava flour is a local Indonesian food that has the potential to reduce the use of wheat flour in making noodles. However, cassava flour has sticky physical characteristics because the high amylopectin may be overcome by adding protein. The purpose of this study is to utilize cassava flour in the manufacture of dried noodles that have good physical characteristics. Another goal is to determine the level of substitution of cassava flour to wheat flour and the addition of a type of protein source and its concentration that can produce the best dry noodles. The research method used was an experimental method by making phase 1 treatments, namely protein type (control / without protein addition, ISP 5%, ISP 10%, egg 5%, egg 10%, egg 15%) in the manufacture of cassava flour substitute dry noodles, and stage 2 treatments namely the level of substitution of cassava flour (20, 30, 40%) and the best protein concentration of stage 1 plus or minus 2.5%). The results showed that the addition of eggs produced dry noodles with better physical and hedonic characteristics than control noodles or noodles with the addition of ISP. The best physical characteristics of noodles result from the addition of 15% eggs. In the Phase 2 experiment it was found that substitution of 20% cassava flour and the addition of 15% eggs produced noodles with the best physical and hedonic characteristics. The dried noodles meet SNI standards and contain 4.50% water, 1.94% ash, 13.7% protein, 2.46% fat, 168.66% water absorption, cooking loss 6.63%, springiness 0, 98 mm, adhesiveness 24.07 gs, and overall hedonic value of 5.25 ± 1.02 (hedonic scale 1-7).